YIELD OF MILLET DEPENDING ON BIOLOGIZATION OF THE GROWING TECHNOLOGY - Каленська, С. М.; Черній, В. П. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
Due to the deepening worldwide ecological crisis, there is a steady increase in the need for food grown under conditions of organic farming. This trend will be deepen and supported by economic interest of manufacturers. That’s why the high demand on today, is the introduction of organic farming, especially if cultivating the millet as the environmentally safe and diet raw materials for making the food products. The research program provided for the optimal way to protect against weeds in crops of millet in the conditions of organic production and study the effect of seed inoculation on growth, development, yield and quality of grain millet varieties studied. It was established that the highest yields of investigated millet varieties was obtained in the application of the chemical method of protection from weed, and seed inoculation by Hetomik. The study found that growing of investigated millet varieties in conditions of Right-Bank Forest- Steppe of Ukraine, without protection from weed and seed inoculation, ensure their productivity at 1,91−2,15 t/ha, while on variants with inoculation seed by Hetomik it was higher by 8,4−13,1 % (2,16−2,33 t/ha). The highest level of productivity was formed by Omriyane, in variants with inoculated seed by Hetomik preparation – 3,49 (chemical), 3,32 (mulch film), 2,96 (mechanical), 2,79 (sawdust mulch), 2,79 (mulching mature mycelium) and 2,45 t/ha (without protection from weeds). With seed inoculation by Humisol Plus preparation, yields on control variant (without dressing) were 2,86−2,99 t/ha, whereas the feeding crops by Humisol Plus (in II, III, VIII stages of organogenesis) increased them in 27,3−30,8 % and amounted to 3,64−3,91 t/ha. Prospects for further research on biologization millet cultivation technology should focus on identifying the most effective way to protect against weeds in agrocenoses, and on studing of the combined effect method of protection from weed, and seed inoculation with using of natural origin agents: Hetomik and Humisol Plus.